2011
DOI: 10.1097/pas.0b013e3182322cf7
|View full text |Cite
|
Sign up to set email alerts
|

“Stealth” Melanoma Cells in Histology-negative Sentinel Lymph Nodes

Abstract: A proportion of patients who develop regional and distant recurrences of melanoma after a pathologically negative sentinel lymph node (SN) biopsy are reported to have enhanced signals for melanoma associated mRNA when sensitive molecular approaches such as RT-PCR are used to evaluate their SN tissue. The significance of these findings remains controversial because the cellular source of the augmented signals cannot be known because the nodal tissue is destroyed during preparation for RT-PCR. Nonetheless it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…Cells similar to the captured CTCs have recently been described in histologically negative sentinel lymph nodes [28]. Itakura et al described 2 subpopulations of melanoma-related cells, which seem analogous to the 2 subpopulations of cells we report here from blood.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Cells similar to the captured CTCs have recently been described in histologically negative sentinel lymph nodes [28]. Itakura et al described 2 subpopulations of melanoma-related cells, which seem analogous to the 2 subpopulations of cells we report here from blood.…”
Section: Resultssupporting
confidence: 86%
“…The putative CTCs consisted of large cells, about half of which stained for both pancytokeratins (pan-KRT) and for CD-45. These captured/cultured melanoma CTCs appear to be analogous to the melanoma-related cells recently been reported in “histologically negative” sentinel lymph nodes [28]. These authors described MLANA-RNA-expressing cells which appeared consistent with melanoma cells, as well as putative macrophage-melanoma hybrids.…”
Section: Discussionsupporting
confidence: 73%
“…Another source of possible FN SLNBx is surgical failure, wherein the operative surgeon fails to identify the SLN or samples non-sentinel lymph nodes in the targeted basin [7,[23][24]. Furthermore, pathologic misclassification has been described as a potential source of FN SLNBx, with re-examination of sentinel lymph nodes demonstrated that 27 to 80% of patients who developed clinical progression of disease secondary to a FN SLNBx had histologic evidence of metastatic disease at the time of initial SLNBx [7,16,25].…”
Section: Etiology Of Fn Sentinel Lymph Node Biopsymentioning
confidence: 97%
“…13,14 Indocyanine green is a small substance molecule (774.96 Da) tricarbocyanine dye and is the only near-infrared fluorophore that is approved by the U.S. Food and Drug Administration for human use. 15 Indocyanine green offers several inherent advantages over other modalities of sentinel lymph node biopsy.…”
Section: Indocyanine Green Spy Elite-assisted Sentinel Lymph Node Biomentioning
confidence: 99%